Aktivitas Antidiabetes Fraksi Dari Ekstrak Etanol Daun Yakon (Smallanthus sonchifolius) Pada Tikus Galur Wistar Yang Diinduksi Aloksan Secara In Vivo - Triana Ariska Dewi; Haryoto Haryoto (Universitas Muhammadiyah Klaten, 2025)
Diabetes mellitus (DM) is a chronic metabolic disorder characterized by persistent hyperglycemia due to impaired insulin secretion or action. Conventional therapy with oral antidiabetic agents and insulin is often associated with adverse effects, including hypoglycemia and gastrointestinal disturbances, which encourage the development of safer alternatives. Yacon (Smallanthus sonchifolius) is known to have antidiabetic potential because it contains fructooligosaccharides (FOS), flavonoids, and phenolic compounds. This study aimed to evaluate the antidiabetic activity of ethanol extract fractions of yacon leaves in alloxan-induced diabetic Wistar rats. The ethanol extract was fractionated into n-hexane, ethyl acetate, and ethanol-water fractions. Male Wistar rats were divided into five groups: negative control, positive control (metformin 100 mg/kgBW), and three treatment groups receiving each fraction (100 mg/kgBW) orally for 21 days. Blood glucose levels were measured on days 0, 7, 14, and 21. Phytochemical screening was conducted using Thin Layer Chromatography (TLC). Data were analyzed using one-way ANOVA followed by LSD test. The results showed that all fractions significantly reduced blood glucose compared to the negative control (p < 0.05). Among them, the ethyl acetate fraction showed the strongest hypoglycemic effect (85.8 ± 5.8 mg/dL at day 21), comparable to metformin (103.2 ± 5.4 mg/dL). TLC analysis confirmed the presence of alkaloids, flavonoids, tannins, and triterpenoids in the ethyl acetate fraction. These compounds are known to act as antioxidants, stimulate insulin secretion, and inhibit glucose absorption. In conclusion, fractions of ethanol extract of yacon leaves, particularly the ethyl acetate fraction, exhibit strong antidiabetic activity and have potential to be developed as natural antidiabetic agents.